Combined use of monensin and virginiamycin to improve rumen and liver health and performance of feedlot-finished steers - Ceconi, Irene (2022)
Monensin and virginiamycin are included in beef cattle finishing diets as prophylaxis to minimize the incidence of ruminal acidosis and liver abscesses. Due to different and probably complementary modes of action, this study aimed to determine the effects of a combination of monensin and virginiamycin, both included in the diet at recommended doses, on ruminal health, the occurrence of liver abscesses, and growth performance of feedlot-finished cattle. One hundred and forty-four steers (6 animals/pen) were fed 1 of 3 corn-based finishing diets containing 30 mg of monensin (MN), 25 mg of virginiamycin (VM), or 30 and 25 mg of monensin and virginiamycin (MN + VM), respectively, per kilogram of dry matter. Ruminal pH probes were inserted into two animals per pen and set to record pH every 10 min. On d 100, animals were slaughtered, and rumens and livers were recovered, on which occurrence and degree of ruminal damage, prevalence and number of liver abscesses, and liver scores (A−: livers with no more than two small abscesses; A+: livers with at least one large abscess or more than four medium abscesses; A: any other abscessed liver) were determined. Simultaneous inclusion of monensin and virginiamycin resulted in a 4.3% decrease (P < 0.04) in dry matter intake (DMI; 8.8, 9.2, and 9.2 ± 0.19 kg/d for MN + VM, MN, and VM-fed animals, respectively) and similar (P > 0.13) average daily body weight gain (ADG; 1.49 ± 0.021 kg/d) and hot carcass weight (HCW; 269 ± 1.7 kg), compared with feeding diets containing one additive or the other. Therefore, in terms of ADG, a 9.4% improvement (P < 0.01) in feed efficiency was observed in MN + VM-fed animals. Backfat thickness (5.6 ± 0.08 mm) and ribeye area (69.9 ± 0.53 cm2) remained unaffected (P ≥ 0.74), as well as the minimum (4.98 ± 0.047), mean (6.11 ± 0.037), and maximum ruminal pH (7.23 ± 0.033) values and the time (125 ± 22.3 min/d), area (57.67 ± 12.383 pH × h), and episodes (22 ± 3.8 bouts) of pH below 5.6 (P ≥ 0.12). Overall, prevalence (24 ± 3.4%) and the number of liver abscesses (1.6 ± 0.14 abscesses/abscessed liver), liver scores (20 ± 3.1% of A− and 4 ± 1.8% of A livers), and prevalence (67 ± 3.5%) and degree of damage to the ruminal epithelium (2.5 ± 0.22% affected surface) were similar (P ≥ 0.18) across treatments; however, the occurrence of ruminal lesions tended (P ≤ 0.07) to be associated with that of liver abscesses and reduced ADG when feeding monensin alone.